THE ROLE of CONSUMER CONFIDENCE AS A MEDIATING INFLUENCE VIRAL MARKETING of VISITING KAMPOENG RADJA JAMBI - Ade Perdana Siregar; Ade Titi Nifita (Journal of Business Studies and Management Review, 2018)
The purpose of this study are: (1) identify the influence between the viral marketing against consumer confidence on the attractions of Kampoeng Radja Jambi, (2) identify the influence between the viral marketing and consumer confidence towards the decision to visit sights Kampoeng Radja Jambi (3) identify the trust was able to mediate the influence of viral marketing of visiting sights Kampoeng Radja Jambi. The population of this research is a community of the city of Jambi whereas samples is a society of the city of Jambi who more than once to visit sights Kampoeng Radja Jambi as much as 150 respondents. Research methods using path analysis. The results of the research that is viral marketing effect significantly to consumer confidence in the sights of Kampoeng Radja Jambi, viral marketing and consumer confidence a significant effect against the decision to visit sights Kampoeng Radja Jambi and consumer confidence can be a mediation against viral marketing influences decisions on visiting sights Kampoeng Radja Jambi